Aspek Rasionalitas Dalam Pengambilan Keputusan Dan Rasionalitas Terbatas (Bounded Rational) - Isra, Al Lukman Syafni; Apriliano, Riko; Prayoga, Arik (CV. ITTC INDONESIA, 2025)
This study aims to analyze classical rationality and bounded rationality as two approaches that explain decision-making processes in various individual, organizational, and public policy contexts. Through a literature review of conceptual and empirical works, this study evaluates the assumption of perfect rationality that emphasizes logical, systematic, and complete information-based decision-making. The analysis then turned to the concept of bounded rationality introduced by Herbert A. Simon and reinforced by Mary Zey's critique, which asserted that human decisions is influenced by cognitive, informational, and environmental limitations. The research findings suggest that individuals tend to use satisficing and heuristic strategies as described by Kahneman and Tversky which, while efficient, can result in systematic biases and decisions that are not always optimal. Recent empirical studies have also shown that bounded rationality has an impact on organizational, managerial, and public policy decisions, and has the potential to cause wrong decisions if cognitive bias is not managed properly. This study concludes that bounded rationality is a more realistic framework than classical rationality, but still requires integration with normative rational approaches to understand decision-making holistically. The implications of this study open up opportunities for further studies that utilize computational approaches and contextual analysis to map decision patterns in real-world situations.